WAIVER OF PENALTY IN THE NEW PENAL CODE - VALENTIN-BOGDAN DANILA (Challenges of the Knowledge Society)
This paper is an attempt to expose the novelty brought by the new Penal Code in relation to both prior criminal law and also with the international law. Thus, one of the most debated articles of the new Penal Code is "giving up penalty" - art. 80-82, which has no counter part in our international law. In this context, the "gain" of this new provision is challenged / contract due to the possible subjective nature of the courts. Relevant in this regard is the fact that deprivation of liberty in the prison environment is a special situation, with strong resonances in the living environment of the defendant, both during detention and afterwards released. Moreover, giving up penalty, is one of the measures individualizing sentences and also a way to deplete its possible negative influences subsumed to the rehabilitation process held in prisons, even with the efforts made by the administration of the detention. Specifically, the "waiver of penalty" intends to alert the authors of criminal deeds with reduced gravity on their obligations regarding future conduct.